上顎前歯部顎骨内に発生した孤立性神経線維腫の1例 - 渡邉, 美貴; 薬師寺, 孝; 片倉, 朗; 柴原, 孝彦; 山本, 雅絵; 橋本, 和彦 (日本口腔外科学会雑誌, 2018)
The 2017 WHO classification of Head and Neck Tumors defines solitary intraosseous neurofibroma of the maxilla (SINM) as an admixture of Schwann cells, fibroblasts, perineurial cells, and axons. Abundant soft tissue is observed in the oral and maxillofacial region, and occurrence in the mandible, and especially in the maxilla, is extremely rare. We report a case of SINM occurring in the anterior tooth region of the maxilla. The patient was a 50-year-old woman who had discomfort in the anterior teeth of the left side of the maxilla and was referred to this department by her personal physician. A biopsy was performed, and a neurogenic tumor was suspected. Maxillary tumor resection and bone transplantation were performed with the patient under general anesthesia. The histopathological examination showed strong positivity for vimentin and positivity for S100 and NSE, and neurofibroma was diagnosed. Two years 7 months have passed since surgery, and there has been no sign of recurrence.